Efek Pre-treatment dalam Larutan Garam sebagai Perlakuan Awal Terhadap Karakteristik Manisan Rebung: Effect of Pre-treatment in Salt Solution as Initial Treatment on Characteristics of Sweet Bamboo Shoot - Fitriarni, Dian; Assroruddin, Assroruddin; Hertalena, Hertalena (Universitas Bumigora, 2025)
Bamboo shoots are a popular food source in Southeast Asia including Indonesia. It is a functional food source but has a taste, odor, and HCN content that requires pre-treatment before processing. The process of processing bamboo shoots into sweets can be an alternative effort to increase vegetable consumption intake for public health. Therefore, a handling method is needed such as soaking in salt solution. The purpose of this study was to study the effect of the soaking process on the quality of bamboo shoot sweets. The method used by soaking bamboo shoots in salt solution with different concentrations (5%, 10%, 15%). The results of the water content of bamboo shoot sweets showed a value ranging from 9.86-22.01%, ash content ranging from 0.03%-0.04%, fiber content of bamboo shoot sweets samples ranging from 1.63-4.02% with sample P3 showing the highest value. The color of the bamboo shoot candy obtained points 5.2-6.3, the aroma ranged from 4.8-6.3, and the texture with a range of points between 5.3-6 the highest value in sample P3 while the taste of the bamboo shoot candy obtained points 5.3-6.2 with the highest value in the 15% salt solution soaking treatment. Based on panelists’ notes, the 10% salt solution soaking treatment obtained a very good response in terms of taste and texture when compared to other treatments.